Years in Cultural Studies: 1983—Stuart Hall Visits Australia and North America - Mariah L Wellman (Lateral, 2019)
Throughout 1983 Cultural Studies continued to spread outside the United Kingdom, spurred by Stuart Hall’s tour of Australia and parts of the United States where he presented lectures connecting current ideas of what it means to study culture in often disparate and intense political climates across the globe. Myriad publications published in 1983 provide insight into how Cultural Studies circulated among scholars in varying disciplines while still in its infancy. This article situates Cultural Studies primarily within a North American context focusing on the pivotal event of the year: the teaching institute held prior to the 1983 conference at the University of Illinois where Hall delivered what would be eight influential lectures in the field of Cultural Studies. Further, I provide insight into an understudied conference held in Australia where Hall’s impact led to the birth of an Australian Cultural Studies journal. Finally, I provide an overview of some of the pivotal publications of the year, connecting ideas of hegemony, power and dominance, reflexivity and Marxism within a western context.